HUBUNGAN KREATIVITAS DALAM KEWIRAUSAHAAN: TINJAU SISTEMATIS: HUBUNGAN KREATIVITAS DALAM KEWIRAUSAHAAN: TINJAU SISTEMATIS - Rani, Putri; Saputra, Tedy Setiawan; Sadikin, Ali (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2023)
This research is a literature review journal which aims to gain an in-depth understanding of creativity and the importance of creativity for an entrepreneur in developing and building a mindset in order to improve a creative mindset. An entrepreneur must be able to compete and always be able to improve the quality of his productivity. One way is by being creative. This research method uses descriptive qualitative research with a systematic literature review approach, by conducting a study of articles published in national journals on the topic of creativity and entrepreneurship. The results of this research show the importance of creativity in entrepreneurship. This is confirmed by previous research which concluded that creativity has a significant effect on entrepreneurship.